Case report: Heterogeneous mutations of SOX10 gene in a Chinese infant with Waardenburg syndrome type 4C - Zhang, Suli; Lin, Shuangzhu; Liu, Zhenxian; Wang, Wanqi; Li, Jiayi; Chen, Qiandui; Yang, Li; Wang, Cui; Pang, Qiming (Frontiers in Pediatrics, 2022)
A5-month-old patient presented with grayish-blue iris (Answer 6 Our patient has heterochromia iris, which presents with a grayish-blue iris bilaterally, and has changed "sclera" in the text to "iris".)bilaterally, skin and mucosal pigmentation loss, Hirschsprung's disease, full-blown growth retardation, and sensorineural deafness. The patient’s whole exon gene sequencing revealed a spontaneous heterozygous code-shifting mutation in the SOX10 gene: c.803del:p.K268Sfs*18. The parents of the child were wild-type, and the site of the mutation is novel.